Screening Test for Olfactory Function: A New Tool Validated in Nepalese Children - Puri, Rupendra; Karki, Puja Thapa; Thapa, Narbada; Prajapati, Anjana; Thapa, Pukar; Pedersen, Babill Stray (Journal of Karnali Academy of Health Sciences, 2021)
Background: Olfactory function disorders adversely affect the growth and development of children and it increases the risk of various injuries and hazards. Despite a significant problem, this area has been neglected and there is no single cross culturally validated tool to evaluate olfactory function of Nepalese children. This study was designed to determine the order recognizable by Nepalese children, which could be used as a screening test tool for olfactory function. Methods: A total of 130 children age ranging from 4 to 10 years from six schools of Kathmandu valley were examined. (Sampling) All students of Nursery to grade 4 were divided into three age groups and tested separately for 22 different odors for the olfactory function. The tested objects were locally available fruits, spices, alcohol, kerosene, baby powder etc. that were selected on the basis of their familiarity with Nepalese children. The objects were kept in a dark labeled coded bottle and unscrewed for smell under nose of each child and at the same time a show card was shown having three pictures including the correct one. The child was then asked to point out the correct answer and was recorded. From the most recognized 12 odors, 7 odors were selected which exceeded the minimum threshold for a proposed screening tool. After two weeks, a revalidation test was carried out among 45 children (15 from each age group) in same schools by using 7 odors in four-fold repetition in order to determine the real identification of odor. Results: Among the 22 objects or odors tested, a 75% recognizability threshold was exceeded by 12 odors. From these 12 orders, 7 most recognized odors (apple, banana, lemon, fish, chocolate, soap and coconut) were selected for a proposed screening test tool. Retesting of the chosen odors showed satisfactory test-retest reliability, split half reliability and validity of the 7 odors test. Conclusion: We found 7 odorants, which were commonly familiar to Nepalese children and can be used to determine the orthonasal olfactory function of Nepalese children. This test is easy, quick, non-interventional and cost effective in resource restricted clinical practice setting like in Nepal